A novel magnetorheological shear-stiffening elastomer with self-healing ability. (10th November 2018) - Wang, Yunpeng; Ding, Li; Zhao, Chunyu; Wang, Sheng; Xuan, Shouhu; Jiang, Han; Gong, Xinglong
Abstract: A novel magnetorheological shear-stiffening elastomer (MSTE) was prepared by dispersing carbonyl iron particles (CIPs) into the shear-stiffening elastomer, which was synthesized by co-polymerization of shear-stiffening gel (STG) and methyl vinyl silicone rubber (VMQ). The storage modulus of MSTE-80 (the volume ratio of STG and VMQ is 80: 20, and 8.5 vol% carbonyl iron) increased 13100% when the frequency increased from 0.1 Hz to 100 Hz in the oscillation shear measurement. Under applying a magnetic field of 960 mT, the storage modulus of MSTE-80 was further strengthened by 425%. Since the reversible interactions of BO bonds, the extensibility of the dissected MSTE-60-d recovered to 423% (the initial extensibility ≈ 1050%) after self-healing at 180 °C for 2 h. Meanwhile, constitutive models based on the standard linear solid model were used to describe the shear-stiffening performance and the viscoelastic nature of MSTEs. Finally, possible mechanisms were proposed to explain the shear-stiffening, magnetorheological, and self-healing properties of MSTEs. It was found that the breakage and reconstruction of BO bonds played a major role in shear-stiffening and self-healing performance. The magnetorheological effects were attributed to the magnetic attraction between the CIPs in the magnetic field.